2021
DOI: 10.1186/s40359-021-00561-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress impact on health outcomes in Gulf War Illness

Abstract: Background Gulf War Illness (GWI) is a chronic, multi-symptomatic disorder affecting an estimated 25–32% of the returning military veterans of the 1990–1991 Persian Gulf War. GWI presents with a wide range of symptoms including fatigue, muscle pain, cognitive problems, insomnia, rashes and gastrointestinal issues and continues to be a poorly understood illness. This heterogeneity of GWI symptom presentation complicates diagnosis as well as the identification of effective treatments. Defining su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
(19 reference statements)
4
13
0
Order By: Relevance
“…This pattern is consistent with prior studies that have shown that GW veterans with PTSD report both a greater number and severity of physical symptoms and medical conditions 33–36 . Additionally, Jeffrey et al (2021) recently showed that GW male veterans with both GWI and PTSD reported worse physical and mental health than veterans with only GWI 37 . Shastry et al (2022) showed the same pattern of results in female veterans 38 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This pattern is consistent with prior studies that have shown that GW veterans with PTSD report both a greater number and severity of physical symptoms and medical conditions 33–36 . Additionally, Jeffrey et al (2021) recently showed that GW male veterans with both GWI and PTSD reported worse physical and mental health than veterans with only GWI 37 . Shastry et al (2022) showed the same pattern of results in female veterans 38 .…”
Section: Discussionsupporting
confidence: 78%
“…[33][34][35][36] Additionally, Jeffrey et al ( 2021) recently showed that GW male veterans with both GWI and PTSD reported worse physical and mental health than veterans with only GWI. 37 Shastry et al (2022) showed the same pattern of results in female veterans. 38 Taken together, these findings suggest that PTSD as a comorbidity identifies a subgroup of GW veterans-including those with GWI-that suffer from a particularly high burden of poor health.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ultimately, these processes have effects beyond the CNS, affecting immune and endocrine function in the periphery and ultimately giving rise to the symptom presentations in the illness. As the presence of PTSD symptoms exacerbates the overall clinical symptoms of GWI [19], and PTSD shows its immunological dysfunction [21][22][23][24], it is reasonable to assume that past trauma may be used to delineate two biological GWI subgroups. In the context of the neuroimmune model presented here, the high and low trauma GWI group blood profiles at rest share the closest proximity with the same altered regulatory state marked by elevated HPA axis activity, depressed HPG activity, depressed NK activity, and increased MK2, CK1, CK17, MK1, MK2, MK6, MK15, CTL, Th17B, and Th17(23) activity, albeit not with complete agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Veterans suffering from GWI are often also diagnosed with post-traumatic stress disorder (PTSD) [16,17]. A population-based study estimates that 35% of veterans with GWI also suffer from PTSD [18], which exacerbates all the overall clinical symptoms of GWI [19]. As there is a substantial overlap of PTSD symptoms with the symptoms defining GWI [20], with both PTSD [21][22][23][24] and GWI [6,25,26] exhibiting immunological dysfunction and abnormal neural synchrony [14], this suggests that GWI and PTSD share several core pathophysiological processes and that these processes may be altered in the context of co-morbidity.…”
Section: Introductionmentioning
confidence: 99%